Avaliação e proposta de formação sobre habilidades básicas para alfabetização de crianças com Trissomia 21 - Muniz, Joice Daiane (2023)
Down syndrome, or Trisomy 21 (T21), is a genetic condition characterized by the presence of an extra chromosome 21, which affects the cognitive and motor development of children with this condition. Learning the prerequisites for literacy is essential, as it involves developing skills such as auditory perception, fine motor skills, and language. These prerequisites are crucial for children with T21 to engage meaningfully in the literacy process. In this context, the present study aims to: (a) characterize teachers' opinions on the basic prerequisites for literacy in children with T21, as well as the implications of these perceptions on planning and pedagogical practice; (b) describe the development level of basic literacy skills in cognition, motor skills, and language; (c) create and implement a collaborative training proposal for teachers, focused on basic literacy skills for children with T21, considering the diversity in the school environment; and (d) evaluate the collaborative training proposal based on teachers' opinions.The study participants were two children with T21, one enrolled in the last stage of Early Childhood Education and the other in the 1st grade of Elementary School, along with their respective teachers. Data collection took place in two schools in a small municipality in the state of São Paulo. The instruments used in the research were: (a) lesson observation guide; (b) initial interview guide for teachers; (c) characterization guide for children with T21 regarding basic literacy skills prerequisites; (d) Motor and Cognitive Development Evaluation Form from the Operationalized Portage Inventory (IPO); (e) a basic literacy skills evaluation protocol based on the IAR; (f) a literacy skills survey protocol based on the Horizontes Method; (g) guide for the collaborative training proposal for teachers; and (h) final interview guide for teachers. The data collected were qualitative and analyzed through category development.The results showed that teachers encouraged the participation of children with T21 in the lessons and were aware that they needed to adapt their pedagogical practices to meet the children's needs, adjusting content and creating appropriate learning materials. Regarding the development level of basic literacy skills in cognition and motor skills, the data revealed that the children with T21 performed below the expected level for their age, with better results in motor skills. The development and implementation of the collaborative training proposal demonstrated the teachers' active involvement in reflecting on their pedagogical practices during the literacy assessment process for children with T21. The training proposal was considered significant in bringing theoretical knowledge related to pedagogical practice and sharing experiences about children with T21.The main considerations highlight the importance of collaborative training proposals, as well as reflections on teachers' opinions and actions regarding the assessment and development of literacy skills for children with T21. The study also emphasizes the importance of building lesson plans, pedagogical practices, and training specifically targeted for these professionals. Therefore, it is essential to create pedagogical practices that promote the literacy process for children with T21 through strategies that support learning, taking into account the collaborative partnership between general education teachers and specialized teachers. Finally, it is suggested that the findings support future studies and guide education professionals in planning, training, and pedagogical practice through collaborative work, ensuring that literacy skills for children with T21 are appropriately addressed.